Perfecting electrocatalysts via imperfections: towards the large-scale deployment of water electrolysis technology. Issue 4 (19th March 2021) - Jiao, Shilong; Fu, Xianwei; Wang, Shuangyin; Zhao, Yong
Abstract : A tuned electronic structure favors the electrocatalytic water splitting reaction via accelerating the reaction kinetics, changing the rate-determining step, and optimizing the adsorption energy for intermediates; this is achieved via intentionally incorporating imperfections into the crystal lattices of electrocatalysts. Abstract : As a potential energy carrier, hydrogen has surged up the priority list as part of broader decarbonization efforts and strategies to build or acquire clean energy economies. Driven by renewable electricity, electrochemical water splitting (WS) promises an ideal long-term, low-carbon way to produce hydrogen, with the ability to tackle various critical energy challenges. To improve the efficiency of electrocatalytic water splitting, electrocatalysts with enhanced conductivity, more exposed active sites, and high intrinsic activity are crucial for decreasing the energy gap for the rate-determining step (RDS) and subsequently improving the conversion efficiency. The incorporation of multidimensional imperfections has been demonstrated to be efficient for modulating the electron distribution and speeding up the electrocatalysis kinetics during electrocatalytic processes and this is now attracting ever-increasing attention. Herein, in this review, we summarize recent progress relating to the regulation of electrical behavior and electron distributions for the optimization of electrocatalytic water-splitting performance via defect engineering. With an emphasis on the beneficial aspects of the hydrogen economy and an in-depth understanding of electron redistribution caused by defect effects, we offer a comprehensive summary of the progress made in the last three to five years. Finally, we also offer future perspectives on the challenges and opportunities relating to water-splitting electrocatalysts in this attractive field.